The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.2478/cttr-2013-0376
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Degradation of Tobacco: VI. Influence of Extraction on the Formation of Some Major Gas Phase Constituents

Abstract: Formation profiles have been determined for the major gas phase constituents formed in an inert atmosphere during the dynamic thermal decomposition of tobaccos extracted with hexane, chloroform, acetone, acetonitrile, and methanol. The profiles include methane, ethane, ethene, propane, propene, isoprene, formaldehyde, acetaldehyde, acetone, 2-butanone, acetonitrile, benzene, and toluene. Except for propene and propane, extraction of tobacco does not dramatically influence either the temperatures for maximum fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 1 publication
1
11
0
Order By: Relevance
“…Acrolein (propenal) (5). The isotopic scrambling experiment showed that 90% of the acrolein derived from Dglucose pyrolysis arose in unimolecular fashion.…”
Section: Overview Of D-glucose Fragmentationmentioning
confidence: 99%
“…Acrolein (propenal) (5). The isotopic scrambling experiment showed that 90% of the acrolein derived from Dglucose pyrolysis arose in unimolecular fashion.…”
Section: Overview Of D-glucose Fragmentationmentioning
confidence: 99%
“…Upon cooling and condensation, enol-acetaldehyde 6 reverts to the carbonyl tautomer 4, which is the observed product under our conditions (Scheme 2). By this unimolecular mechanism, C-2 of glycerin specifically ends up as the aldehyde carbon of acetaldehyde (4). The Cyclic Grob Fragmentation would be expected to be available for operation in either the gas phase or a condensed phase.…”
Section: Change Of Mechanistic Preference Over Time; Effect Of Additivesmentioning
confidence: 99%
“…Such chemistry is also relevant to the formation of cigarette smoke [4]. The mechanisms involved in this chemistry are therefore of considerable importance to understand.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate pyrolysis is of central importance in the thermochemical conversion of biomass to sources of energy [1][2][3], the formation of flavors during the cooking of food [4], and in the formation of cigarette smoke constituents generated from carbohydrates in tobacco by the act of smoking [5,6]. Yet despite this importance, much of the detailed chemistry remains poorly understood, and the pathways of product formation of numerous pyrolysis products remain debatable [7].…”
Section: Introductionmentioning
confidence: 99%